ANALYSIS OF THE INCIDENT RATE OF PEOPLE WITH A POTENTIAL RISK FOR HYPERTENTION AND DIABETES IN KENJERAN SUB-DISTRICT, SURABAYA - Maya Septriana; Aliyah Siti Sundari; Diyantoro Diyantoro; Dwi Wahyu Indriati; Anita Kurniati; Ni Nyoman Purwani; Tofan Agung Eka Prasetya; Fadilatus Sukma Ika Noviarni; Shelly Wulandari; Myrna Adianti (Darmabakti Cendekia: Journal of Community Service and Engagements, 2019)
Background: The number of people with diabetes mellitus in Indonesia is increasing every year. The data in 2016 showed that 1 of 11 adults could have diabetes mellitus. Uncontrolled and untreated diabetes mellitus can cause complications. Objectives: This activity aimed to determine the group of age that have a potential risk of hypertension and diabetes so that it could minimize the prevalence of disease and optimize human productivity. Methods: (1) Counseling about hypertension and diabetes, (2) Screening the people with a potential risk of hypertension using tensimeter and diabetes prediction using point-of-care testing (POCT) and urine dipstick. Results: The data were collected from 75 respondents with characteristics about 85,33% female and 14,67% male. About 25 respondents (33,33%) were suspected of hypertension. Based on age group, it showed that the highest incident rate of hypertension was found in the age group of 41-60 years (41,86%), followed by the age group of 61-80 years (20%), 21-40 years (13,33%), and age under 20 years and above 80 years (0%). The majority of respondents had a normal glucose level(90,67%). Based on gender, there was 1 male respondent (9,09%)and5female respondents  (7,81%) having a glucose level higher than normal value (hyperglycemia). Conclusion:  The age group with the highest potential risk for hypertension was 41-60 years, while for diabetes was 61-80 years. This activity provided information to prevent the potential risk leading to hypertension and diabetes.